KOMUNITAS ETNIK TIONGHOA DI KOTA RANTAUPRAPAT KABUPATEN LABUHANBATU - Sri Anugerah Lestari; Ria Anjelita Simbolon; Abd. Haris Nasution; Mhd. Ihsan Syahaf Nasution (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This article aims to find out about the existence of the Chinese ethnic community in Rantauprapat City, Labuhanbatu Regency. Especially regarding the beginning of his arrival, socio-economic life to the role of the ethnic Chinese community in socio-economic development in the city of Rantauprapat, Labuhanbatu Regency. To obtain the necessary data, the researcher used a historical research method consisting of four stages, namely, heuristics, source criticism, data interpretation and historiography. Then the data collection technique is carried out by observing the research location, interviews with the community or residents around the research location, especially with Chinese people who have long inhabited this area, then literature study through books, journals and articles, as well as documentation. by collecting supporting images or photos. The results showed that the ethnic Chinese community in the city of Rantauprapat, Labuhanbatu district came through shipping activities which were driven by the unfavorable economic conditions at that time. Basically in this area the most ethnic immigrants are ethnic Chinese. Where this ethnic has mingled with the local indigenous people. It is undeniable that the presence of Chinese people in Rantauprapat has contributed to the development of this area, especially in the economic field.